Surgical management of chronic pain. Issue 2 (February 2017) - Oesman, Chenur; Shieff, Colin
Abstract: Chronic pain is believed to affect around 14 million people in England. It impacts on society and places a high demand on healthcare with an estimated cost to the UK National Health Service £10 billion per annum. Management of chronic pain is therefore a major clinical challenge. Many patients will be managed effectively in community or primary care while a proportion will require specialist secondary and tertiary care pain services. For these a multidisciplinary approach with pharmacological and non-pharmacological strategies will improve quality of life but there will still be a proportion with significant symptoms that cannot be helped in this fashion. Selected patients with intractable pain may benefit from targeted surgical procedures, reducing the long-term physical, emotional and financial burden that results from their situation. The technical and clinical challenge is determining 'who', 'what', 'where' and 'when' in order to provide the best possible long-term outcome and quality of life. Over the past three decades, with the exception of procedures for trigeminal neuralgia, the bias in neurosurgical intervention for chronic pain relief has changed from ablative lesioning towards reversible, low-risk neuromodulation techniques wherein electrical stimulation of part of the nervous system or intrathecal medication is used to control pain or modify physiology.